Urokinase plasminogen activator (uPA) and plasminogen activator inhibitor type-1 (PAI-1) in breast cancer - Lampelj, Maja (Radiology and oncology (Ljubljana), 2015)
Background. Urokinase plasminogen activator (uPA) and plasminogen activator inhibitor type-1 (PAI-1) play a key role in tumour invasion and metastasis. High levels of both proteolytic enzymes are associated with poor prognosis in breast cancer patients. The purpose of this study was to evaluate the correlation between traditional prognostic factors and uPA and PAI-1 expression in primary tumour of breast cancer patients. Patients and methods. 606 primary breast cancer patients were enrolled in the prospective study in the Department of gynaecological oncology and breast oncology at the University Medical Centre Maribor between the years 2004 and 2010. We evaluated the traditional prognostic factors (age, menopausal status, tumour size, pathohistological type, histologic grade, lymph node status, lymphovascular invasion and hormone receptor status), together with uPA and PAI-1. We used Spearman%s rank correlation, Mann Whitney U test and X2 test for statistical analysis. Results. Our findings indicate a positive correlation between uPA and tumour size (p < 0.001), grade (p < 0.001), histological type (p < 0.001), lymphovascular invasion (p = 0.01) and a negative correlation between uPA and hormone receptor status (p < 0.001). They also indicate a positive correlation between PAI-1 and tumour size (p = 0.004), grade (p < 0.001), pathohistological type (p < 0.001) and negative correlation between PAI-1 and hormone receptor status (p = 0.002). Conclusions. Our study showed a relationship between uPA and PAI-1 and traditional prognostic factors. Their role as prognostic and predictive factors remains to be further evaluated.
Keywords: aktivator plazminogena; breast; breast cancer; dojke; plasminogen activator inhibitor; plazminogen; rak (medicina); urokinase plasminogen activator; urokinaza